Disparitas Kematian Maternal di Indonesia: Studi Ekologi dengan Analisis Spasial - Rahmah Hida Nurrizka; Tri Yunis Miko Wahyono (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
This study is an analyze disparity of maternal mortality in Indonesia with spatial analysis using intermediatefactor such as maternal health service, reproduction status, socio economic and demography. This studyaimed to spatially analyze disparity of maternal mortality, analyze the influence and risk of maternal mortality onintermediate factors, and provide recommendations on maternal health problems in Indonesia. This study usingecological study design (agrerat studies), spatial analysis, bivariate analysis, and multivariate analysis. Unit ofanalysis in this study is districts/cities in Indonesia. The results showed that disparity of maternal mortality causedby intermediate factor gap between districts/cities in Indonesia, with the highest risk of maternal mortality occurredin eastern Indonesia. The dominant variables related to maternal mortality, namely population density withOR:0,283 (95% CI:0,185-0,430) and childbirth by skilled health personal with OR:1,745 (95% CI:1,081-2,815).The high risk of maternal mortality occurred in districts/cities with low coverage of fourth pregnancy (K4), lowbirth attendance (PN) coverage, low postpartum (KF) coverage, average number of children, low average education,and high poverty